Sistema administrativo – operativo y su incidencia en la rentabilidad de la empresa Bjf trading S.A. Año 2014. Manual de Gestión. - Culcay Veliz, Marisol Belén (2016)
The present work was carried out in the Cooperativa de Ahorro y Crédito Quevedo LTDA., In order to evaluate the administrative and financial situation of the cooperative, in the recovery of the portfolio, it was considered its internal and external development, corresponding to the placement of credit Granted and subsequent portfolio recovery. Since the cooperative is a financial institution, the portfolio analysis is fundamental in its daily activity through administrative-financial management. For the investigation, the manager and credit directors of the Quevedo Credit Union, were also interviewed. Surveys were also made to the institution's partners, as well as secondary information such as: brochures, writings, books, policies and regulations. The institution, regulations of the superintendency of popular and solidarity economy. The SPSS 19.0 program was used to tabulate the data and analyze the results obtained. In the study carried out by means of a survey and interview with the credit function players of the Credit Union Quevedo Ltda., The answers were obtained that reveal the situation of the cooperative on the high levels of portfolio closing to the year 2015 with $ 1,797 .423.91, having already been reduced by 13.8% compared to 2014. For all of the above, an operational loan manual was presented, focused on the sustainable improvement of the institution based on a process management with continuous training according to To the financial market in addition to the regulations of the control bodies.